Internet addiction among middle school students, causes and treatments - Aaday Jaber Kazem Al-Quraishi (Zanco Journal of Humanity Sciences)
The aim of this research is to identify the Internet addiction for the intermediate school students, the reasons and the treatments, and was based on the definition of (Ward,2000) in the construction of the scale, which is of (20) paragraph, has been verified the characteristics of the  psychometric measure of the discriminatory force and check the validity of the tool (0.80) and in the internal consistency method Alpha Kronbach (0.78). The researcher applied the standard to the middle school students in Wasit governorate / Azizia district. The sample was selected by the random stratified method of the Azizia Directorate of Education for the year Study (2018/2019), has The researcher used the statistical bag (SPSS) to measure the concept of his research, and the results of the research that the students have addiction to the Internet, and that there are differences of statistical significance according to the gender variable and for the benefit of male students.